Changing Effects of Minimally Invasive Surgical Intervention on ALT, AST, and UA in Patients with Obstructive Sleep Apnea-Hypopnea Syndrome. (14th July 2022) - Yu, Liang-Cai; Zhao, Xin; Liu, Li-Jun; Li, Xiao-Ying; Zhou, Jin; Zeng, Ping; Zhang, Xiao-Qing
Abstract : Background . This study aims at exploring the effect of obstructive sleep apnea–hypopnea syndrome (OSAHS) on the liver and kidney function indexes of patients and analyze the changes in these indexes after minimally invasive surgery. Method . Patients with OSAHS ( n = 51) who were diagnosed via polysomnography (PSG) and received minimally invasive surgery in the sleep disorders diagnosis and treatment center of the West China Fourth Hospital of Sichuan University from January 2017 to January 2019 were selected as test subjects and placed in the OSAHS group. At the same time, 79 healthy people with no snoring or breathing difficulties were selected from the medical examination center of the hospital as the control group (tested as normal by PSG). These two groups were used to compare the differences in the related indexes of serum liver and kidney function and evaluate the changes in sleep monitoring and related liver and kidney function indexes in patients with OSAHS after minimally invasive surgery. Results . The alanine aminotransferase (ALT), aspartate aminotransferase (AST), and uric acid (UA) levels were higher in the OSAHS group (48.98 ± 36.34, 28.88 ± 14.80, and 422.30 ± 98.65, respectively) than in the control group (21.91 ± 11.61, 22.18 ± 6.19, and 330.49 ± 64.45 and t = 6.514, 3.549, and 6.373, respectively; p < 0.05 ). Of the patients with OSAHS, 17 were followed up for one year. After minimally invasive surgery, ALT decreased from 44.29 ± 20.61 to 26.47 ± 9.91 ( t = 4.395), AST decreased from 27.71 ± 8.32 to 21.82 ± 4.81 ( t = 3.673), and UA decreased from 397.35 ± 92.14 umol/L to 362.94 ± 106.76 umol/L ( t = 2.580), and these differences were statistically significant (p < 0.05 ).The changes in ALT ( r = −0.635) and AST ( r = −0.504) were related to the difference in the lowest blood oxygen saturation (p < 0.05 ), and the change in UA was related to the difference in the apnea–hypopnea index ( r = −0.532, p < 0.05 ). Conclusion . There are some abnormalities in liver- and kidney-function-related indexes in patients with OSAHS, and minimally invasive surgery can help to improve liver and kidney function in these patients.